Pemberdayaan Masyarakat melalui Budidaya Tanaman Porang di Desa Kambuno Kecamatan Bulukumpa Kabupaten Bulukumba - Hasnidar; St. Nasriah; Suma, Mansyur (Universitas Islam Negeri Alauddin Makassar, 2025)
This study discusses two important things, namely first, how is the role of the government in empowering the community through porang plant cultivation in Kambuno Village, Bulukumpa District, Bulukumba Regency. Second, what are the obstacles faced in empowering the community through porang plant cultivation in Kambuno Village, Bulukumpa District, Bulukumba Regency. This study uses a qualitative method with descriptive analysis and a sociological approach. Data collection techniques used include direct observation, interviews, and documentation in Kambuno Village, Bulukumpa District, Bulukumba Regency. Data sources in this study consist of primary and secondary data. The data analysis techniques applied include the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of the government in empowering the community through porang cultivation in Kambuno Village, Bulukumpa District, Bulukumba Regency is not yet optimal and requires improvement. The role carried out in this empowerment includes socialization to the community and assistance to porang farmers. However, there are still obstacles faced such as a relatively long time for the initial harvest, lack of information on community knowledge regarding the selection of the right type of seeds and fertilizers, pest and disease disturbances, difficulties in obtaining quality porang information, limited land, and unstable price fluctuations. The implications of this study are expected for the government, both village heads, BUMDes and members of farmer groups to play a more active role and facilitate the community in empowering porang cultivation in Kambuno Village, Bulukumpa District, Bulukumba Regency.